2021
DOI: 10.3390/agronomy11122588
|View full text |Cite
|
Sign up to set email alerts
|

Germinated Chickpea and Lupin as Promising Ingredients for Breadmaking—Rheological Features

Abstract: Improving the alpha-amylase activity of wheat flour represents an opportunity to valorize wheat grains of low baking quality. In this sense, germinated legumes can be used to increase enzymatic activity, giving superior final product characteristics at the same time. The aim of this study was to underline the effects of chickpea (CGF) and lupin germinated flours (LGF) added simultaneously to white wheat flour on the rheological behavior of dough and to evaluate an optimal product microstructure. For this purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The determinations were performed in the range of linear viscoelasticity at constant stress of 50 Pa in a frequency sweep from 1 to 20 Hz. The creep and recovery tests had a time of 60 s and 120 s, respectively [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determinations were performed in the range of linear viscoelasticity at constant stress of 50 Pa in a frequency sweep from 1 to 20 Hz. The creep and recovery tests had a time of 60 s and 120 s, respectively [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The 2 substances had the role of specific fluorescent dyes, fluorescein to detect starch and rhodamine B for proteins. After placing the samples in the immersion solution, they were examined with the help of ImageJ software (v. 1.45, National Institutes of Health, Bethesda, MD, USA) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to Wandersleben et al, the use of nongerminated lupine flour up to 10% in wheat flour did not negatively affect the bread quality [11]. The uses of germinated lupine flour (GLF) in combination with germinated chickpea in breadmaking have been previously reported by Atudorei et al [20], who concluded that germinated legume flour addition leads to a decrease of dough consistency and an increase in dough elasticity. For this reason, the aim of our study is to analyze the effect of GLF on dough rheological properties, microstructure and bread quality.…”
Section: Introductionmentioning
confidence: 90%
“…Research on germinated rice flour (for 24 h) and legumes (chickpeas, lupine) has shown adequate functionality to be used as a raw ingredient in the manufacture of GF bread, helping to improve the texture and colour of bread (Cornejo and Rosell 2015). Although germinated seeds have multiple benefits in food, more research is needed to improve GF products' texture and sensory properties and gain wider consumer acceptance (Atudorei et al 2021).…”
Section: Dough Technologiesmentioning
confidence: 99%